2016
DOI: 10.3390/ijerph13010110
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Study of Association between Heavy Metals and Itchy Eyes, Coughing in Chronic Cough Patients: Related with Non-Immunoglobulin E Mediated Mechanism

Abstract: The association between heavy metals exposure and respiratory diseases or allergic sensitization showing high serum immunoglobulin E (IgE) has been suggested. However, previous findings have been inconsistent and the mechanisms responsible remain unclear. We evaluated heavy metal exposure and its association with coughing, itchy eyes in chronic cough patients with different IgE levels. Ninety outpatients in Kanazawa University Hospital were recruited between January–June 2011. Subjects whose total IgE measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 66 publications
0
6
1
Order By: Relevance
“…Although multiple studies have reported associations between pollutants and cutaneous disease, the underlying mechanism remains unclear (Araviiskaia et al, 2019;Kim et al, 2016;Weng et al, 2017). Previous studies have described non-IgEemediated mechanisms of pruritus with heavy metal exposure, suggesting that heavy metals may have a direct role that needs to be elucidated in further studies (Nguyen et al, 2016;Weng et al, 2017). Whereas our results reveal an age differential between our cohorts, previous literature reveals no association between age and blood heavy metal levels (Chang et al, 2018).…”
Section: Elevated Blood Heavy Metals In Pruritic Dermatosescontrasting
confidence: 69%
See 1 more Smart Citation
“…Although multiple studies have reported associations between pollutants and cutaneous disease, the underlying mechanism remains unclear (Araviiskaia et al, 2019;Kim et al, 2016;Weng et al, 2017). Previous studies have described non-IgEemediated mechanisms of pruritus with heavy metal exposure, suggesting that heavy metals may have a direct role that needs to be elucidated in further studies (Nguyen et al, 2016;Weng et al, 2017). Whereas our results reveal an age differential between our cohorts, previous literature reveals no association between age and blood heavy metal levels (Chang et al, 2018).…”
Section: Elevated Blood Heavy Metals In Pruritic Dermatosescontrasting
confidence: 69%
“…Tannery workers with increased serum chromium (P < 0.05) were found to have increased cutaneous complaints of rough skin, itch, and rash (P < 0.001; Islam et al, 2019). Ocular pruritus was also found to be associated with aerial heavy metal exposure (Nguyen et al, 2016). Finally, blood lead levels have been found to be a positive predictor of uremic pruritus in patients undergoing hemodialysis (Weng et al, 2017).…”
Section: Elevated Blood Heavy Metals In Pruritic Dermatosesmentioning
confidence: 97%
“…It has been considered that these organic and inorganic pollutants were simultaneously long-range transported to Japan by westerly winds. They are thought to be common causes of hospital admission for respiratory, cerebrovascular, and cardiovascular diseases [10], cough prevalence [11][12][13], itchy eyes [14], asthma exacerbation [15], and seasonal allergic rhinitis [7,16].…”
Section: Introductionmentioning
confidence: 99%
“…This cough is usually sudden and irritating, and it may lead to a sudden increase in blood pressure, tachycardia, and pneumothorax, and especially in the absence of strict fasting, the gastric contents could reflux into the mouth, causing life-threatening asphyxia via inhalation into the lungs. 4 Thus, finding an effective way to suppress cough is of important clinical significance.…”
Section: Introductionmentioning
confidence: 99%